2013
DOI: 10.1159/000353445
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Variation for Topic Shift and Other Functions in Local Contrasts in Conversation

Abstract: Speakers and listeners have been shown to use phonetic cues to help them in tracking the ongoing structure of conversational interaction, but fragmentation between qualitative and quantitative research means that the forms and functions of these cues have been given varying characterizations. The current study explores prosodic variation in contrastive structures in conversational data, using a combined methodology adopting aspects from both qualitative (conversation analysis) and quantitative (experimental ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Many previous studies focused on the correlations of formal, measurable features and the underlying communicative or linguistic phenomena such as speech acts [15], topic structure [16,21] and some paralinguistically relevant properties like age, gender and expressed emotions of the speakers [17]. Beyond the theoretical questions, the main practical challenge of these studies is how we can make the content -which is readily accessible for humans -machine-readable (detectable or predictable) based on physically measurable acoustic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies focused on the correlations of formal, measurable features and the underlying communicative or linguistic phenomena such as speech acts [15], topic structure [16,21] and some paralinguistically relevant properties like age, gender and expressed emotions of the speakers [17]. Beyond the theoretical questions, the main practical challenge of these studies is how we can make the content -which is readily accessible for humans -machine-readable (detectable or predictable) based on physically measurable acoustic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Discourse topic is also not part of a binary opposition as is the case for the notions of topic and focus, or theme and rheme. More substantial reviews of topic in diff erent theoretical ameworks can be found in Berthoud (1996), Goutsos (1997), Grobet (2002) and Zellers (2013). I concentrate here on putting together an understanding of discourse topic suited to interactional data and systematic analyses.…”
mentioning
confidence: 99%
“…A lot of work has been devoted to the notion of discourse topic, but many studies investigated only one type of topic transition or topic sequence, such as topic transitions operated over a contrastive structure (Zellers, 2013) or stepwise topic 13 transitions (Jeff erson, 1984). Other studies took a semasiological approach and inquired into the role that a specifi c linguistic form can play in topic structure, such as fi gurative expressions (Holt & Drew, 2005), new referents (Geluykens, 1993;Gundel et al, 1993), discourse markers (Fraser, 2009), or prosody (Nakajima & Allen, 1993;Zellers, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations